Challenges of Indonesian Halal Industry in the Digital Economic Era - KN. Sofyan Hasan; Taroman Pasyah (Sriwijaya Law Review, 2022)
Food is the most important basic human need, and its fulfilment is part of the human rights of every Indonesian people. Food must always be available in a sufficient, safe, quality, nutritious, varied manner at a price that is affordable by people's purchasing power and is halal given the religion and beliefs of the community, especially Muslims. The awareness of Muslim consumers in Indonesia regarding halal products continues to increase. However, there are interesting facts about the current pattern of fast food and beverages consumption due to technological advances in today's digital economy. This article examines the challenges of the Indonesian halal industry in the digital economy era. The method used in this study is a juridical or normative approach, such as an approach to legislation and literature relevant to the halal industry. As a result, the law on halal product guarantees emphasises that the challenge for the Indonesian halal industry in this digital economy era is the obligation of halal certification for all food and beverage products. Unfortunately, the regulation is not serious enough to be enforced by the government because it is not supported by the ease and low cost of making a halal certification, coupled with a lack of public awareness. So the halal industry in the form of fast food and beverages in Indonesia, especially in today's digital economy, is still difficult to obtain. Thus, to obtain a halal food and beverage industry in this digital economy era, the alternative is that there must be a special institution that issues and supervises halal certification of food and beverage products that will circulate in the community and synergise with the government.